Pengaruh Kompetensi dan Motivasi Kerja terhadap Kinerja Pegawai pada Sub Bagian Tata Usaha Direktorat Pendidikan Khusus dan Pendidikan Layanan Khusus - Fakhri Rahman Azzura; Suharini Suharini (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
Employee performance is a fundamental factor in determining the success of a government agency in achieving the organization's vision and mission. Low employee performance is often caused by a lack of adequate competence and weak work motivation. Competencies include knowledge, skills, and attitudes that are relevant to the task, while work motivation reflects internal and external motivations that affect the level of effort of employees in carrying out their responsibilities. This study aims to analyze the extent to which competence and work motivation can affect employee performance in the Administration Sub-Division of the Directorate of Special Education and Special Service Education. The research method used was a quantitative approach with the distribution of questionnaires to 46 respondents, consisting of employees within the agency. The results of the partial test (t-test) showed that competence had a significant influence on employee performance (t-count = 2.049 > t-table = 2.016; sig. 0.047). Similarly, work motivation exerted a significant influence (t-count = 3.763 > t-table = 2.016; sig. 0.001). Simultaneously, the F-test proved that competence and work motivation had a significant effect together (F-count = 11.003 > F-table = 3.214; sig. 0.000). The value of the determination coefficient (R Square) of 0.339 indicates that 33.9% of employee performance variations can be explained by competence and work motivation, while the rest is influenced by other factors such as work environment, leadership, and reward system. The practical implications of this study emphasize the importance of improving employee competencies through continuous training, as well as effective motivational strategies such as incentivization, rewards, and strengthening communication. This effort is expected to be able to create optimal and sustainable performance in supporting the achievement of organizational goals.